An Unmodulated Very-Low-Voltage Electrosurgical Technology Creates Predictable and Ultimate Tissue Coagulation: From Experimental Data to Clinical Use. (October 2020) - Watanabe, Yusuke; Fuchshuber, Pascal; Homma, Takafumi; Bilgic, Elif; Madani, Amin; Hiki, Naoki; Cammack, Ivor; Noji, Takehiro; Kurashima, Yo; Shichinohe, Toshiaki; Hirano, Satoshi
Objective. We analyzed the underlying principles of an unmodulated very-low-voltage (VLV) mode, designated as "soft coagulation" in hemostasis, and demonstrate its clinical applications. Summary Background Data . While the advantage of the VLV mode has been reported across surgical specialties, the basic principle has not been well described and remains ambiguous. Methods . Characteristics of major electrosurgical modes were measured in different settings. For the VLV mode, the tissue effect and electrical parameters were assessed in simulated environments. Results . The VLV mode achieved tissue coagulation with the lowest voltage compared with the other modes in any settings. With increasing impedance, the voltage of the VLV mode stayed very low at under 200 V compared with other modes. The VLV mode constantly produced effective tissue coagulation without carbonization. We have demonstrated the clinical applications of the method. Conclusions. The voltage of the VLV mode consistently stays under 200 V, resulting in tissue coagulation with minimal vaporization or carbonization. Therefore, the VLV mode produces more predictable tissue coagulation and minimizes undesirable collateral thermal tissue effects, enabling nerve- and function-preserving surgery. The use of VLV mode through better understanding of minimally invasive way of using electrosurgery may lead to better surgical outcomes.